Anticandidal, Antioxidant, Toxicity Studies And Isolation Of Compounds From Cassia Fistula Seeds - Subramanion, Jo Thy Lachumy (2011)
In the present study, methanol seeds extract of Cassia fistula was assayed for antimicrobial and antioxidant activities, isolated and purified for bioactive compounds as well as evaluated for the toxicity effect. The seeds extract was tested for potential antimicrobial activity against medically important Gram-positive and Gram-negative bacteria and fungal strains. The antimicrobial activity was determined by the disc diffusion and the broth dilution methods. The extract was effective on tested microorganism and the minimum inhibitory concentration (MIC) values were found in the range of 1.563-50.00 mg/mL. The seeds extract showed a favourable activity against pathogenic fungi C. albicans with MIC value 6.25 mg/mL, and this was confirmed by time kill assay study.